Immunogenicity risk assessment for biotherapeutics through in vitro detection of CD134 and CD137 on T helper cells - Sivan Cohen; Srividya Myneni; Anna Batt; Joyce Guerrero; Jochen Brumm; Shan Chung (Taylor & Francis Group, 2021)
Biotherapeutics, which are biologic medications that are natural or bioengineered products of living cells, have revolutionized the treatment of many diseases. However, unwanted immune responses still present a major challenge to their widespread adoption. Many patients treated with biotherapeutics develop antigen-specific anti-drug antibodies (ADAs) that may reduce the efficacy of the therapy or cross-react with the endogenous counterpart of a protein therapeutic, or both. Here, we describe an in vitro method for assessing the immunogenic risk of a biotherapeutic. We found a correlation between clinical immunogenicity and the frequency with which a biotherapeutic stimulated an increase in CD134, CD137, or both cell surface markers on CD4+ T cells. Using high-throughput flow cytometry, we examined the effects of 14 biotherapeutics with diverse rates of clinical immunogenicity on peripheral blood mononuclear cells from 120 donors with diverse human leukocyte antigen class II-encoding alleles. Biotherapeutics with high rates of ADA development in the clinic had higher proportions of CD4+ T cells positive for CD134 or CD137 than biotherapeutics with low clinical immunogenicity. This method provides a rapid and simple preclinical test of the immunogenic potential of a new candidate biotherapeutic or biosimilar. Implementation of this approach during biotherapeutic research and development enables rapid elimination of candidates that are likely to cause ADA-related adverse events and detrimental consequences.